For a CPS-IoT Enabled Healthcare Ecosystem Consider Cognitive Cybersecurity - Anggy Giri Prawiyogi; Lista Meria (Pandawan Sejahtera Indonesia, 2023)
Cyber-Physical Systems (CPS)-Internet of Things (IoT) enable healthcare services and infrastructure to enhance human lives, but they are vulnerable to various emerging cyber attacks. Cybersecurity specialists struggle to keep up with increasingly sophisticated attack methods. An urgent requirement exists for inventive cognitive cybersecurity in CPS-IoT enabled healthcare ecosystems. This paper presents a framework for cognitive cybersecurity to simulate human cognitive behavior in anticipating and responding to new and evolving cybersecurity and privacy threats to CPS-IoT and critical infrastructure systems. The framework encompasses the conceptualization and description of a layered architecture that integrates Artificial Intelligence, cognitive methods, and innovative security mechanisms.